EVALUASI PENERAPAN SAK ETAP DALAM PELAPORAN ASET BIOLOGIS PADA PETERNAKAN UNGGUL FARM BOGOR - Ranny Catary Cahyani; Vita Aprilina (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2014)
This research aims to evaluate the implementation of SAK-ETAP in the reporting of biological assets at Unggul Farm Bogor Plantation. This research use descriptive-evaluative method that describe measurement, recognition and presentation of biological assets. Document techniques is used to collect data related to biological asset owned Unggul Farm Bogor Plantation then compared it with SAK ETAP. Unggul Farm Bogor Plantation has not present cash flow statement yet. Biological assets in Unggul Farm Bogor Plantation are growing animal, one day old chicken, 48 weeks broilers, and reject eggs. They are recognized as inventory, measured at cost and presented at balance sheet. Chicken breeders (chicken at production period) and immature breeding flocks (growth chicken) are recognized as other current asset, measured at cost and presented at balance sheet.